2021
DOI: 10.1016/j.tranon.2021.101028
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose naltrexone plays antineoplastic role in cervical cancer progression through suppressing PI3K/AKT/mTOR pathway

Abstract: Highlights LDN inhibited proliferation in cervical cancer. LDN inhibited migration and invasion in cervical cancer cells. LDN mediated the propagation property in cervical cancer through PI3K/AKT/mTOR signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“… Hela, Siha, C33A and Caski human cervical cancer cell lines were purchased from the Cell Bank of the Chinese Academy of Sciences ALB/C nude mice (4–6 weeks old) were purchased from Charles River (Beijing, China) LDN was dissolved in DMEM to 0.5, 1.5, 2, 3, and 5 mg/mL, and the culture was continued for 24, 48, and 72 h The mice were randomly divided into four groups with five animals in each group, including the control group, the 0.5 mg/kg group, the 5 mg/kg group, and the 10 mg/kg group based on the concentrations of LDN administered to the mice every day Suppressed the proliferation, migration and invasion abilities and promote apoptosis in Hela cells Inhibit cervical cancer progression in nude mice. Reduced the number of TAMs, mainly M2 macrophages, and decreased expression of anti-inflammatory factor IL-10 in the serum of nude mice Low-dose naltrexone plays antineoplastic role in cervical cancer progression through suppressing PI3K/AKT/mTOR pathway [ 47 ]. Human cervical cancer cell lines Hela and Siha (TCHu187 and TCHu113) were purchased from the Cell Bank of the Chinese Academy of Sciences 4 × 106 Hela cells (in 0.1 ml solution) were injected into BABL/c nude mice.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… Hela, Siha, C33A and Caski human cervical cancer cell lines were purchased from the Cell Bank of the Chinese Academy of Sciences ALB/C nude mice (4–6 weeks old) were purchased from Charles River (Beijing, China) LDN was dissolved in DMEM to 0.5, 1.5, 2, 3, and 5 mg/mL, and the culture was continued for 24, 48, and 72 h The mice were randomly divided into four groups with five animals in each group, including the control group, the 0.5 mg/kg group, the 5 mg/kg group, and the 10 mg/kg group based on the concentrations of LDN administered to the mice every day Suppressed the proliferation, migration and invasion abilities and promote apoptosis in Hela cells Inhibit cervical cancer progression in nude mice. Reduced the number of TAMs, mainly M2 macrophages, and decreased expression of anti-inflammatory factor IL-10 in the serum of nude mice Low-dose naltrexone plays antineoplastic role in cervical cancer progression through suppressing PI3K/AKT/mTOR pathway [ 47 ]. Human cervical cancer cell lines Hela and Siha (TCHu187 and TCHu113) were purchased from the Cell Bank of the Chinese Academy of Sciences 4 × 106 Hela cells (in 0.1 ml solution) were injected into BABL/c nude mice.…”
Section: Methodsmentioning
confidence: 99%
“…The same authors postulate that low-dose NTX could upregulate the expression of OGFr. Furthermore, low-dose NTX indirectly reduced the expressions of phosphatidylinositol-3-kinase (PI3K/AKT), pAKT and mTOR in vitro and in vivo [ 47 ].…”
Section: Effect On Oncologic Outcomesmentioning
confidence: 99%
“…Lycorine promoted apoptosis of gastric tumor cells by FBXW7-MCL1 axis [31]. Low-dose naltrexone inhibited PI3K/AKT/mTOR pathway and thus suppressed the proliferation of cervical cancer cells [32]. Tanespimycin acted as an antineoplastic drug through targeting HSP90 [33].…”
Section: Agingmentioning
confidence: 99%
“…The time of significant difference in mice treated with 0.5 mg/kg LDN was 34 days [74] LDN 0.5 mg/kg, LDN 5 mg/kg, LDN 10 mg/kg…”
Section: Ldn In In Vitro and In Vivo Experimental Modelsmentioning
confidence: 99%
“…Based on the results of the CCK-8 test, it was concluded that LDN can inhibit cancer cell proliferation in a time- and dose-dependent manner. The effect of LDN on the regulatory abilities of migration and invasion of the aforementioned cell lines was then examined, demonstrating that LDN treatment could significantly reduce the migration of Hela cells [ 74 ].…”
Section: Naltrexonementioning
confidence: 99%